Conducting Correctional Speech Therapy Work with Preschool Children with Autism Spectrum Disorders Using Neuropsychological Technologies - Boytemirova Saboxat MaXammadi qizi; Zulfiya Mamarajabova Narbayevna (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2026)
This article examines the theoretical and practical aspects of applying correctional speech therapy using neuropsychological technologies for preschool children with autism spectrum disorders. The study reveals the psychological, neurological, and linguistic characteristics of autism spectrum disorders and, based on scientific evidence, identifies the specific patterns of speech development in this group of children. Particular attention is given to analyzing the impact of the neuropsychological approach on the speech therapy process, especially the implementation of technologies aimed at improving sensory integration, enhancing cognitive functions, stimulating motor activity, and facilitating verbal communication. The article demonstrates the effectiveness of correctional speech therapy conducted with the use of neuropsychological technologies and scientifically substantiates their positive impact on children’s speech activity, social adaptation, cognitive development, and emotional stability. The research findings indicate that a comprehensive neuropsychological and speech therapy approach is essential for restoring and improving speech functions, developing communication skills, and facilitating children’s adaptation to the educational process. This study has significant scientific and practical value in the fields of preschool education, special pedagogy, speech therapy, and neuropsychology, and it is aimed at developing methodological recommendations for specialists.